Social Inequality, Childhood and the Media A Longitudinal Study of the Mediatization of Socialisation - Paus-Hasebrink, Ingrid (Transforming Communications - Studies in Cross-Media Research, 2019)
This open access book presents a qualitative longitudinal panel-study on child and adolescent socialisation in socially disadvantaged families. The study traces how children and their parents make sense of media within the context of their everyday life over twelve years (from 2005 to 2017) and provides a unique perspective on the role of different socialisation contexts, drawing on rich data from a broad range of qualitative methods. Using a theoretical framework and methodological approach that can be applied transnationally, it sheds light on the complex interplay of factors which shape children's socialisation and media usage in multiple ways.